Rekrutmen Dan Seleksi Tenaga Pendidikan (Guru) Untuk Meningkatkan Kualitas Pendidikan di SMA Unggulan Berbasis Pesantren Amanatul Ummah Pacet - mizanul Hasanah (Pendidikan Agama Islam, Fakultas Ilmu Tarbiyah dan Keguruann, IAIN Syekh Nurjati Cirebon, 2020)
The main purpose of recruitment and selection is to get educators who are able to realize the goals of education, especially in Indonesia. This policy is a very important first step and needs to be implemented by all educational institutions in order to maintain the expected quality of education. Data collection techniques carried out by observation, interviews, and documentation. The results of this study indicate that (1) the recruitment carried out in the High Schools Based on Pesantren Amanatul Ummah Pacet is held every year. Whether it aims to find new teachers with vacant positions or positions or additional positions. (2) Selection is carried out in the High Schools Based on the Islamic Boarding School of Amanatul Ummah Pacet conducted after the recruitment with the aim of determining the criteria for prospective educators / teachers according to the needs of the institution. When recruitment has been carried out, the applicants will then pass the selection stage. (3) One way to improve the quality of education in the High Schools Based on Pesantren Amanatul Ummah Pacet is through a good recruitment and selection process. Among others, by selecting superior products through recruitment and selection of teachers who are selective / rigorous which aims to produce quality superior products).